Environmental Performances of a Timber-concrete Prefabricated Composite Wall System. (May 2017) - Fortuna, Stefano; Mora, Tiziano Dalla; Peron, Fabio; Romagnoni, Piercarlo
Abstract: The improvement of environmental performance in building construction could be achieved by prefabrication. This study quantifies and compares the environmental impacts of a Concrete Glulam Framed Panel (CGFP): the basic configuration of this precast component consists in a Cross-Laminated Timber (CLT) frame structure supporting a thin reinforced concrete slab with an interior insulation panel and covered by finishing layers. The research investigates also alternative design of configuration with the substitution of different insulation materials in order to minimize the Embodied Energy and Carbon Footprint values. The boundary of the quantitative analysis is "cradle to gate" including the structural support system; an IMPACT 2002+ characterization methodology is employed to translate inventory flows into impacts indicators. Results present very low values for carbon footprint (60.63 kg CO2 eq m -2 ) and the embodied energy values (919.44 MJ m -2 ) indicate this hybrid precast structure as a valid alternative building constructions and processes. A detailed discussion of the outputs is presented, including the comparison of the environmental performances depending on different insulation materials.